OPPORTUNITIES FOR USING THE OUTSOURCING MODEL IN THE RECRUITMENT AND SELECTION OF YOUNG PROFESSIONALS FOR THE PUBLIC CIVIL SERVICE - Kholov A.Kh; Isroilov I.K (Scholar Express Journals, 2025)
This article provides an in-depth analysis of the opportunities for employing the outsourcing model in the processes of attracting and selecting young specialists for public civil service. The research highlights both theoretical and practical aspects of the role of outsourcing in the personnel selection system, its contribution to efficiency, and its application in public administration practice. In addition, the article pays attention to new trends in the labor market and the qualification requirements for young personnel, analyzing how well outsourcing services align with these needs and exploring the economic and organizational aspects of implementing them in practice. As one of the main directions of the study, foreign experiences—particularly those of Japan and European countries—are examined, with a focus on the possibilities of adapting these practices to the national context. On this basis, the article substantiates the advantages of using outsourcing mechanisms to optimize the personnel selection process in the public civil service, to develop the innovative potential of young people, and to introduce modern management principles. The results of the article scientifically justify the relevance of utilizing outsourcing services in the public administration system, demonstrating that this approach creates new opportunities for the effective recruitment of young specialists into public service and for their professional development. Moreover, the article provides a theoretical analysis of the legal and organizational foundations of the outsourcing process and develops concrete scientific recommendations regarding the prospects for the development of this model.
Keywords: public civil service; young specialists; personnel selection